World Bank's poverty reduction strategy paper approach : good marketing or good policy? - Levinsohn, Jim (UNCTAD WashingtonUS, 2003)
Reviews the Poverty Reduction Strategy Paper (PRSP) approach. Discusses what the PRSP is. Reviews the recent mid-term evaluations of the PRSP approach conducted both internally by the World Bank and the IMF as by external organizations.